BLOCKCHAIN TECHNOLOGY IN UZBEKISTAN TAX ADMINISTRATION SYSTEM - Melikhurozov Bexruz Bekzod ugli; Ida Farida Adi Prawira (Innovation Science and Technology, 2025)
This article explores the potential integration of blockchain technology into Uzbekistan’s tax administration system. It begins by addressing the challenges faced by the current system, such as inefficiencies, lack of transparency, and corruption. The paper highlights the core features of blockchain, including decentralization, immutability, and transparency, and explains how these can revolutionize tax collection and auditing. It also discusses possible use cases, such as real-time transaction tracking, fraud prevention, and smart contracts for automated tax processes. The article examines global examples of blockchain application in taxation and considers the economic benefits for Uzbekistan, such as enhanced compliance and increased government revenues. Challenges such as infrastructure limitations, regulatory frameworks, and public adoption are also analyzed. Finally, it provides a forward-looking perspective on how blockchain can drive digital transformation in Uzbekistan’s tax system, fostering greater efficiency and trust.